Laminate and method for producing the same, packaging bag and package
The laminate with a solvent-free adhesive composition and an adhesive strength of 1.0N/15mm or more addresses the issue of poor tearability in digital printing laminates by ensuring sufficient adhesion between layers, thereby enhancing tearability and reducing environmental impact.
Patent Information
- Application Number
- JP2023159960
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-04-04
AI Technical Summary
Digital printing using electrostatic ink compositions often results in laminates with insufficient adhesive strength between the electrostatic ink layer and the primer or adhesive layer, leading to delamination and poor tearability, especially when external forces are applied.
A laminate structure comprising a substrate film, a primer layer, an adhesive layer with a solvent-free adhesive composition containing a polyol component and a polyisocyanate component, and a sealant film, where the adhesive layer has an adhesive strength of 1.0N/15mm or more, ensuring sufficient adhesion between the electrostatic ink layer and the adhesive layer.
The laminate achieves excellent tearability while reducing environmental impact, as the solvent-free adhesive composition enhances the adhesive strength and prevents delamination, even under external forces.
Smart Images

Figure 2025051058000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate and a manufacturing method thereof, a packaging bag, and a package. [Background technology]
[0002] Packaging bags for containing and sealingly storing beverages, foodstuffs, and the like are known. Packages using thin films or sheets are used as packaging bags. Various information such as product, brand, manufacturer, and the like is printed on such packaging bags. As a means for such printing, a digital printer using an electrostatic ink composition is known.
[0003] For example, Patent Document 1 proposes applying a primer resin to a first flexible substrate such as a PET film to obtain a coating surface, performing electrostatic printing on the coating surface using a digital printer (Indigo 20000 label and packaging digital printer manufactured by HP), and applying a crosslinking composition. It is known that the adhesive strength of a laminate including an electrostatic ink layer formed by such digital printing is reduced. Therefore, Patent Document 2 proposes using a cured product of a polyol, a polyisocyanate, and an epoxy compound as an adhesive layer as a laminate capable of maintaining a sufficiently high adhesive strength between layers even under high-temperature hot water conditions such as retort treatment.
[0004] On the other hand, from the viewpoint of reducing the environmental load, adhesives that do not contain organic solvents are being developed. For example, Patent Document 3 proposes a two-component curing solventless adhesive containing a polyisocyanate component and a polyol component, and a composite film for packaging foods, beverages, medicines, quasi-drugs, etc. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2018-530478 [Patent Document 2] International Publication No. 2021 / 024981 [Patent Document 3] JP 2011-162656 A Summary of the Invention [Problem to be solved by the invention]
[0006] Digital printing using an electrostatic ink composition is capable of handling small lot production, and therefore digitally printed laminates are used as materials for various packaging bags. However, the electrostatic ink layer provided by a digital printer may not have sufficient adhesive strength with the primer layer or adhesive layer, and there is a concern that the tearability between the electrostatic ink layer and the primer layer or adhesive layer may be deteriorated when an external force is applied. For example, when a laminate with insufficient interlayer adhesion is torn, delamination may occur between the electrostatic ink layer and the primer layer or adhesive layer. Such delamination occurs because the external force when tearing the laminate cannot be fully utilized to tear the substrate. Therefore, it is considered that a laminate with insufficient interlayer adhesion is prone to delamination when torn, resulting in poor tearability.
[0007] In addition, conventional organic solvent-based adhesive layers use organic solvents, which raises concerns about the burden on the environment. In view of this, the present disclosure provides a laminate having an electrostatic ink layer, which has excellent tearability while reducing the environmental burden, and a method for producing the same. In addition, the present disclosure provides a packaging bag and a packaging body including such a laminate. [Means for solving the problem]
[0008] One aspect of the present disclosure provides a laminate comprising a base film, a primer layer, an adhesive layer, and a sealant film in this order, and a printed surface of an electrostatic ink composition adhered to the adhesive layer, wherein the adhesive layer comprises a solventless adhesive composition containing a polyol component and a polyisocyanate component, a cured product thereof, or a mixture of these, and the adhesive layer has an adhesive strength of 1.0 N / 15 mm width or more.
[0009] Since the electrostatic ink composition used in digital printing machines has a lower strength than other inks, the adhesive strength of the adhesive layer adjacent to the electrostatic ink layer is low, and delamination is likely to occur when torn, which is thought to be one of the factors that deteriorate the tearability. The above laminate has an adhesive strength of 1.0 N / 15 mm width or more, so that the adhesive layer and the electrostatic ink layer are sufficiently bonded, and even a laminate having a solvent-free adhesive layer has excellent tearability. In addition, the solvent-free adhesive layer can reduce the environmental load.
[0010] One aspect of the present disclosure provides a method for producing a laminate, the method comprising the steps of: forming a primer layer on one side of a substrate film; printing an electrostatic ink composition on the primer layer to obtain a printed surface; adhering the printed surface and a substrate including a sealant film using a solventless adhesive composition including a polyisocyanate component and a polyol component; and curing or semi-curing the adhesive composition to form an adhesive layer having an adhesive strength of 1.0 N / 15 mm width or more.
[0011] Since the electrostatic ink composition used in digital printing machines has a lower strength than other inks, the adhesive strength of the adhesive layer adjacent to the electrostatic ink layer is low, and delamination is likely to occur when torn, which is thought to be one of the factors that deteriorate the tearability. The manufacturing method of the above laminate includes a step of curing or semi-curing the adhesive composition so that the adhesive strength of the adhesive layer is 1.0 N / 15 mm width or more. This allows the adhesive layer and the electrostatic ink layer to be sufficiently bonded, and even if the laminate uses a solvent-free adhesive composition, the tearability is sufficiently excellent. In addition, the use of a solvent-free adhesive layer can reduce the environmental load.
[0012] One aspect of the present disclosure provides a packaging bag formed by heat-sealing the sealant films in the above-mentioned laminate. The packaging bag has the above-mentioned laminate, and thus has a solvent-free adhesive layer, while the adhesive layer has sufficiently high adhesive strength. Therefore, it is possible to provide a packaging bag that reduces environmental load and has excellent tearability. In addition, since digital printing (electrostatic printing) can be used, the design freedom of the packaging bag can be sufficiently increased.
[0013] One aspect of the present disclosure provides a package including the above-mentioned packaging bag and an item to be contained in the packaging bag. The packaging bag has the above-mentioned laminate, and thus has a solvent-free adhesive layer while the adhesive layer has sufficiently high adhesive strength. Therefore, it is possible to provide a packaging bag that reduces environmental load and has excellent tearability. In addition, since digital printing (electrostatic printing) can be used, the design freedom of the packaging body can be sufficiently increased. Effect of the Invention
[0014] It is possible to provide a laminate having an electrostatic ink layer, which has excellent tearability while reducing the environmental impact, and a manufacturing method thereof. It is also possible to provide a packaging bag and a packaging body including such a laminate. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a cross-sectional view showing an example of a laminate. [Diagram 2] FIG. 4 is a cross-sectional view showing another example of a laminate. [Diagram 3] FIG. 2 is a plan view showing an example of a packaging bag and a packaging body. [Figure 4] FIG. 11 is a perspective view showing another example of a packaging bag. [Diagram 5] FIG. 4 is a diagram showing a part of a tear surface when a laminate is torn. [Figure 6] FIG. 4 is a diagram showing a part of a tear surface when a laminate is torn. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present disclosure will be described with reference to the drawings as needed. However, the following embodiment is an example for explaining the present disclosure, and is not intended to limit the present disclosure to the following content. In the description, the same reference numerals are used for the same elements or elements having the same functions, and redundant description is omitted as the case may be. In addition, the positional relationship such as up, down, left, right, etc. is based on the orientation of the reference numerals shown in the drawings, unless otherwise specified. Furthermore, the dimensional ratio of each element is not limited to the ratio shown in the drawings.
[0017] Unless otherwise specified, the materials exemplified in this disclosure can be used alone or in combination of two or more. When there are multiple substances corresponding to each component in the composition, the content of each component in the composition means the total amount of the multiple substances present in the composition, unless otherwise specified. In this disclosure, a numerical range indicated using "~" indicates a range including the respective numerical values described before and after "~" as the minimum and maximum values. In this disclosure, the upper limit and lower limit values indicated individually can be arbitrarily combined.
[0018] <Laminate> Fig. 1 is a cross-sectional view showing an example of a laminate. Fig. 1 shows a cross section along the lamination direction (thickness direction) of the laminate. The laminate 300 has a base film 10, a primer layer 40, an electrostatic ink layer 50, an adhesive layer 30, and a sealant film 20, in this order. The primer layer 40 and the electrostatic ink layer 50 are in contact with each other, and the electrostatic ink layer 50 and the adhesive layer 30 are in contact with each other.
[0019] The substrate film 10 may have a flexible substrate. The flexible substrate may include, for example, one or both of a metal foil such as an aluminum foil and a thermoplastic polymer in the form of a film. Flexible substrates include biaxially oriented polypropylene (OPP), biaxially oriented polypropylene (BOPP), polyethylene terephthalate (PET), oriented polyamide (OPA), solid polypropylene (CPP), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), and nylon film.
[0020] The base film 10 may include, for example, a vapor deposition film (transparent vapor deposition film) having a resin layer such as a PET film and a barrier layer (vapor deposition layer) on the resin layer. This can improve the sealing property when the laminate 300 is used as a packaging material. Examples of the barrier layer include a metal foil, a vapor deposition layer of a metal (e.g., aluminum) or a metal oxide (e.g., silica or alumina), and the like. The thickness of the base film 10 may be 7 to 150 μm, 10 to 100 μm, or 12 to 80 μm. A specific example of the transparent vapor deposition film is a transparent vapor deposition PET film in which a transparent vapor deposition layer is formed on a PET film. The base film 10 may include a nylon film such as a barrier nylon film.
[0021] The primer layer 40 may contain a resin. Examples of the resin include polyvinyl alcohol resin, cellulose-based resin, polyester, polyamine, polyethyleneimine resin, polyamide resin, polyurethane, polyacrylic polymer, hydroxyl-containing resin, carboxyl-containing resin, and amine-based polymer. By having the primer layer 40, printing of the electrostatic ink composition using a digital printer can be smoothly performed. In addition, the adhesion of the electrostatic ink layer 50 to the primer layer 40 can be improved. The application amount of the resin constituting the primer layer 40 is, for example, 0.01 to 1.5 g / m. 2 and may be 0.05 to 1.0 g / m 2 may be also possible.
[0022] The laminate 300 has a printing surface 52 on the primer layer 40. An electrostatic ink layer 50 is provided on the printing surface 52. The electrostatic ink layer 50 may be composed of an electrostatic ink composition. The electrostatic ink layer 50 is provided by electrostatic printing using a digital printing machine. As shown in FIG. 1, the electrostatic ink layer 50 may be provided so as to cover a part of the surface of the primer layer 40. That is, the electrostatic ink layer 50 may be provided so as to be interspersed between the primer layer 40 and the adhesive layer 30. This allows the laminate 300 to have blank areas.
[0023] The electrostatic ink layer 50 may be of a single color, or may be formed by laminating a plurality of electrostatic ink compositions having different colors. The electrostatic ink layer 50 and the adhesive layer 30 are adjacent to each other. In this example, the heights of the plurality of electrostatic ink layers 50 are the same, but this is not limited thereto. The electrostatic ink layer 50 may be a plurality of layers, or may be continuous into one layer. In this example, the electrostatic ink layer 50 is interrupted in the lateral direction of FIG. 1. The interrupted portion of the electrostatic ink layer 50 becomes a blank portion. In another example, the electrostatic ink layer 50 may be formed without interruption, and the laminate may have no portion where the adhesive layer 30 and the primer layer 40 are in direct contact with each other.
[0024] The thickness of the electrostatic ink layer 50 can be adjusted by changing the ink coverage. The ink coverage represents the ratio of the dot area per unit area. For example, when a certain area is uniformly printed in a single color, the ink coverage is 100%. On the other hand, the ink coverage of an area where no printing is performed (plain area) is 0%. The ink coverage can be calculated based on these two. For example, the ink coverage can be 200% when the ink is applied once, and 300% when the ink is applied twice. In this way, the ink coverage can be increased by increasing the number of times the ink is applied. When only half of the entire area is printed once, the ink coverage is 50%. When printing is performed using ink of multiple colors, the ink coverage can be calculated for each color ink, and the total of the ink coverages can be used as the ink coverage of the target electrostatic ink layer 50.
[0025] The ink coverage is set by a digital printer (e.g., HP's Indigo 20000 label and packaging digital printer) and can be adjusted by specifying a desired value in the ink coverage setting. The ink coverage on the printing surface 52 can be confirmed by observing the printing surface 52 with an optical microscope.
[0026] The ink coverage may be 500% or less, 400% or less, 300% or less, or 200% or less. Such ink coverage reduces the thickness of the electrostatic ink layer, and the adhesive strength of the adhesive layer can be further increased. Such a laminate has better tearability. The ink coverage may be 10% or more, or 100% or more.
[0027] The electrostatic ink composition constituting the electrostatic ink layer 50 is an ink composition used in liquid electrophotographic printing, i.e., electrostatic printing, and is printed on the primer layer 40. The electrostatic ink composition may contain a colorant or pigment such as a dye, and a resin. In addition to these, the electrostatic ink composition may also contain a carrier fluid or carrier liquid. It may further contain a charge director, a charge adjuvant, a surfactant, a viscosity modifier, an emulsifier, and other additives. It may also contain a component that permeates through the adhesive layer 30 (e.g., a polyisocyanate component).
[0028] Examples of colorants include cyan pigments, magenta pigments, yellow pigments, and black pigments. From the viewpoint of facilitating digital printing, a resin having a relatively low melting point (for example, 100° C. or less) can be used as the resin. Examples of the resin include thermoplastic resins such as ethylene acrylic acid copolymer, propylene acrylic acid copolymer, ethylene methacrylic acid copolymer, propylene methacrylic acid copolymer, and ethylene vinyl acetate copolymer. It is preferable that the resin contains at least one of ethylene acrylic acid copolymer and ethylene methacrylic acid copolymer.
[0029] Carrier fluids and carrier liquids include hydrocarbons, silicone oils, vegetable oils, and the like. Hydrocarbons include aliphatic hydrocarbons, branched aliphatic hydrocarbons, and aromatic hydrocarbons. The electrostatic ink composition may be substantially free of carrier liquid when printed onto a print substrate, such as a first substrate. The carrier liquid may be removed, for example, by an electrophoretic process or evaporation during printing, thereby transferring substantially only solids to the print substrate.
[0030] Charge directors serve to maintain a sufficient electrostatic charge on the particles contained in the electrostatic ink composition and include, for example, ionic compounds such as metal salts of fatty acids, metal salts of sulfosuccinates, metal salts of oxyphosphates, metal salts of alkylbenzenesulfonic acids, metal salts of aromatic carboxylic or aromatic sulfonic acids, as well as zwitterionic and non-ionic compounds such as polyoxyethylenated alkylamines, lecithin, polyvinylpyrrolidone, and organic acid esters of polyhydric alcohols.
[0031] The charge adjuvant has the effect of increasing or stabilizing the charge of particles contained in the electrostatic ink composition. Examples of the charge adjuvant include barium petronate, calcium petronate, naphthenic acid Co salt, naphthenic acid Ca salt, naphthenic acid Cu salt, naphthenic acid Mn salt, naphthenic acid Ni salt, naphthenic acid Zn salt, naphthenic acid Fe salt, stearate Ba salt, stearate Co salt, stearate Pb salt, stearate Zn salt, stearate Al salt, stearate Cu salt, stearate Fe salt, and metal carboxylates.
[0032] The electrostatic ink composition may contain a crosslinked product crosslinked by a component contained in the adhesive layer 30. This can sufficiently increase the strength of the electrostatic ink layer 50 itself, as well as the adhesive strength between the electrostatic ink layer 50 and the adhesive layer 30. In addition, it can suppress the occurrence of gaps at the interface between the electrostatic ink layer 50 and the adhesive layer 30. This can improve the adhesive strength of the adhesive layer 30, and can provide a laminate 300 with excellent tearability.
[0033] The thickness of the adhesive layer 30 may be 0.5 to 5 μm, 0.6 to 3 μm, or 0.8 to 2 μm, which allows a good balance between adhesive strength and design.
[0034] The thickness of each layer constituting the laminate 300 can be measured by observing a cross section of the laminate 300 with a digital microscope.
[0035] The adhesive layer 30 may be composed of a solvent-free adhesive composition, a cured product thereof, or a mixture thereof. The adhesive composition may be a two-component curing type. The adhesive layer 30 contains two components, a polyisocyanate component and a polyol component. At least a part of these components may react with each other to form a cured product. The cured product may contain polyurethane. The adhesive layer 30 containing the above two components is in direct contact with the electrostatic ink layer 50. By being a solvent-free adhesive, the environmental load can be reduced. In addition, the polyol component and the polyisocyanate component contained in the adhesive composition penetrate into the electrostatic ink layer, coagulate the electrostatic ink composition, sufficiently increase the adhesive strength, and it is possible to obtain a laminate 300 that is less likely to cause interlayer delamination when torn and has sufficiently excellent tearability.
[0036] The polyisocyanate component may contain a hexamethylene diisocyanate derivative (hereinafter, sometimes referred to as an "HDI derivative"). It is considered that the hexamethylene diisocyanate derivative has a tendency to easily penetrate or become compatible with the electrostatic ink layer. This can further increase the cohesive force of the electrostatic ink layer 50, further increase the adhesive strength of the adhesive layer 30, and obtain a laminate 300 with further excellent tearability. The HDI derivative may be a bifunctional derivative of hexamethylene diisocyanate. The HDI derivative is an aliphatic diisocyanate, and is more likely to penetrate into the electrostatic ink layer 50 than aromatic diisocyanates. For this reason, the electrostatic ink layer 50 and the adhesive layer 30 become compatible with each other well, and the crosslinking effect of the adhesive layer 30 and the electrostatic ink layer 50 is improved. This improves the adhesion between the electrostatic ink layer 50 and the adhesive layer 30.
[0037] The HDI derivative may be a trifunctional derivative of HDI (hexamethylene diisocyanate). Such a trifunctional derivative penetrates the electrostatic ink layer 50 and crosslinks with the components of the electrostatic ink layer 50. This increases the cohesive force of the electrostatic ink layer 50, and further increases the adhesive strength of the laminate 300. By including both a bifunctional derivative and a trifunctional derivative as the HDI derivative, the HDI derivative can be sufficiently penetrated into the electrostatic ink layer 50 and the crosslinking reaction with the components of the electrostatic ink layer 50 can be further advanced, so that even if the thickness of the electrostatic ink layer 50 is large, the adhesive strength of the adhesive layer 30 can be maintained sufficiently high, and the laminate 300 having even better tearability can be obtained.
[0038] In the adhesive layer 30 (adhesive composition), the content of the trifunctional derivative of HDI may be higher than the content of the bifunctional derivative of HDI. This allows a crosslinking reaction to proceed in the adhesive layer 30 and the electrostatic ink layer 50, improving the strength of the adhesive layer 30 and the electrostatic ink layer 50, and also allowing the adhesive force between the adhesive layer 30 and the electrostatic ink layer 50 to be sufficiently increased. Therefore, a laminate 300 having even better tearability can be obtained. From this viewpoint, the mass ratio of the trifunctional derivative to the total of the bifunctional derivative and the trifunctional derivative may be 55 mass% or more, or may be 60 mass% or more. On the other hand, from the viewpoint of maintaining the flexibility of the adhesive layer 30 and the electrostatic ink layer 50, the mass ratio of the trifunctional derivative to the total of the bifunctional derivative and the trifunctional derivative may be 85 mass% or less, 80 mass% or less, or 75 mass% or less. An example of the mass ratio of the trifunctional derivative to the total of the bifunctional derivative and the trifunctional derivative is 55 to 85 mass%.
[0039] Examples of HDI derivatives include HDI multimers (e.g., dimers, trimers, pentamers, heptamers, etc.), biuret modified products (e.g., biuret modified products produced by the reaction of HDI with water, tertiary alcohols, or amines), allophanate modified products (e.g., allophanate modified products produced by the reaction of HDI with alcohols), urea modified products (e.g., urea modified products produced by the reaction of HDI with diamines), oxadiazinetrione (e.g., oxadiazinetrione produced by the reaction of HDI with carbon dioxide), carbodiimide modified products (carbodiimide modified products produced by decarboxylation condensation reaction of HDI), polyol modified products, etc. Also, an adduct of HDI and trimethylolpropane may be used.
[0040] The content of the HDI derivative in the polyisocyanate component may be 15% by mass or more, 20% by mass or more, or 25% by mass or more. This allows the above-mentioned effects to be fully exhibited. The content of the HDI derivative in the polyisocyanate component may be 60% by mass or less, 50% by mass or less, or 40% by mass or less. An example of the content of the HDI derivative in the polyisocyanate component is 15 to 60% by mass.
[0041] The polyisocyanate component may further contain a polyisocyanate having two or more isocyanate groups in one molecule, which is different from the HDI derivative. This allows the laminate 300 to be flexibly designed according to the desired properties. Examples of such polyisocyanate monomers include aromatic diisocyanates, aromatic alicyclic diisocyanates, aliphatic diisocyanates, and alicyclic diisocyanates.
[0042] Aromatic diisocyanates are highly reactive and easily cured, which allows the laminate 300 to be rapidly manufactured. Examples of aromatic aliphatic diisocyanates include m- or p-phenylene diisocyanate or a mixture thereof, 2,4- or 2,6-tolylene diisocyanate or a mixture thereof (TDI), 4,4'-, 2,4'-, or 2,2'-diphenylmethane diisocyanate or a mixture thereof (MDI), 4,4'-toluidine diisocyanate (TODI), 4,4'-diphenyl ether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate (NDI), and the like.
[0043] Examples of the aromatic aliphatic diisocyanate include 1,3- or 1,4-xylylene diisocyanate or a mixture thereof (XDI), 1,3- or 1,4-tetramethylxylylene diisocyanate or a mixture thereof (TMXDI), ω,ω'-diisocyanato-1,4-diethylbenzene, and the like.
[0044] Examples of the aliphatic diisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, 1,2-, 2,3- or 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, and the like.
[0045] Examples of alicyclic diisocyanates include 1,3-cyclopentene diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (isophorone diisocyanate; IPDI), 4,4'-, 2,4'-, or 2,2'-dicyclohexylmethane diisocyanate or a mixture thereof (hydrogenated MDI), methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 1,3- or 1,4-bis(isocyanatomethyl)cyclohexane or a mixture thereof (hydrogenated XDI), and the like.
[0046] The polyisocyanate component may contain a derivative of the polyisocyanate monomer (polyisocyanate derivative). Examples of the polyisocyanate derivative include polyisocyanate derivatives (e.g., dimers, trimers, pentamers, heptamers, etc.), allophanate modified products (e.g., allophanate modified products produced by the reaction of a polyisocyanate monomer with alcohols, etc.), biuret modified products (e.g., biuret modified products produced by the reaction of a polyisocyanate monomer with water or amines, etc.), urea modified products (e.g., urea modified products produced by the reaction of a polyisocyanate monomer with a diamine, etc.), oxadiazinetrione (e.g., oxadiazinetrione produced by the reaction of a polyisocyanate monomer with carbon dioxide gas, etc.), and carbodiimide modified products (carbodiimide modified products produced by decarboxylation condensation reaction of a polyisocyanate monomer, etc.).
[0047] The polyisocyanate component may include an isocyanate-terminated prepolymer. The isocyanate-terminated prepolymer is a urethane prepolymer having at least two isocyanate groups at the molecular end. The urethane prepolymer can be obtained by subjecting at least one member selected from the group consisting of a polyisocyanate monomer, a polyisocyanate derivative, and an isocyanate-terminated prepolymer to a urethane reaction with a polyol.
[0048] The polyol component may contain at least one selected from the group consisting of polyester polyols and polyether polyols. Among these, from the viewpoint of reducing production costs and suppressing hydrolysis, polyether polyol may be contained.
[0049] The polyether polyol may be a polyalkylene oxide. For example, it may be obtained by addition reaction of an alkylene oxide such as ethylene oxide and / or propylene oxide with a low molecular weight polyol as an initiator. Specific examples include polyethylene glycol, polypropylene glycol, and polyethylene polypropylene glycol (random or block copolymer). In addition, for example, polytetramethylene ether glycol obtained by ring-opening polymerization of tetrahydrofuran may be mentioned.
[0050] The polyester polyol can be obtained, for example, by a condensation reaction or an ester exchange reaction between a polyhydric alcohol and a polybasic acid, its alkyl ester, its acid anhydride, or its acid halide. Examples of the polyhydric alcohol include a low molecular weight diol, a low molecular weight triol, and a low molecular weight polyol having four or more hydroxyl groups.
[0051] Examples of low molecular weight diols include ethylene glycol, propylene glycol, trimethylene glycol, 1,4-butylene glycol, 1,3-butylene glycol, 1,2-butylene glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2,2-dimethyl-1,3-propanediol, neopentyl glycol, 1,6-hexanediol, 2,2-diethyl-1,3-propanediol, 3,3-dimethylolheptane, and 2-ethyl-2-butyl-1,3-propanediol.
[0052] Examples of low molecular weight triols include glycerin, 2-methyl-2-hydroxymethyl-1,3-propanediol, 2,4-dihydroxy-3-hydroxymethylpentane, 1,2,6-hexanetriol, trimethylolethane, trimethylolpropane, 2-methyl-2-hydroxymethyl-1,3-propanediol, 2,4-dihydroxy-3-(hydroxymethyl)pentane, and 2,2-bis(hydroxymethyl)-3-butanol.
[0053] Examples of low molecular weight polyols having four or more hydroxyl groups include tetramethylolmethane, pentaerythritol, dipentaerythritol, D-sorbitol, xylitol, D-mannitol, and D-mannite.
[0054] Examples of the alkyl ester of a polybasic acid include methyl ester and ethyl ester of a polybasic acid. Examples of the acid anhydride include acid anhydrides derived from a polybasic acid. For example, oxalic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, 2-alkyl (C12-18) succinic anhydride, tetrahydrophthalic anhydride, and trimellitic anhydride can be mentioned.
[0055] The acid halide may be an acid halide derived from the above-mentioned polybasic acid, such as oxalic acid dichloride, adipic acid dichloride, or sebacic acid dichloride.
[0056] In the adhesive layer 30 (adhesive composition), the mass ratio of the polyisocyanate component may be higher than the mass ratio of the polyol component. Specifically, the mass ratio of the polyisocyanate component to the polyol component may be 1 or more, 1.2 or more, or 1.4 or more. In this way, by increasing the mass ratio of the polyisocyanate component to the polyol component, the curing reaction is promoted and the adhesion and curing process can be sufficiently shortened. From the same viewpoint, the mass ratio of the polyisocyanate component to the polyol component may be 4 or less, or 3 or less. One example of the mass ratio of the polyisocyanate component to the polyol component is 1 to 4.
[0057] Examples of the sealant film 20 include a non-oriented polypropylene film (CPP film), a linear low-density polyethylene film (LLDPE film), and a low-density polyethylene film (LDPE film). The thickness of the sealant film 20 may be 10 to 150 μm, 20 to 100 μm, or 30 to 80 μm.
[0058] FIG. 2 is a cross-sectional view showing another example of the laminate. FIG. 2 shows a cross-section along the lamination direction (thickness direction) of the laminate. The laminate 310 has a base film 10, a primer layer 40, an electrostatic ink layer 51, a first adhesive layer 30, an intermediate layer 21, a second adhesive layer 31, and a sealant film 20 in this order. The primer layer 40 and the electrostatic ink layer 51 are in contact with each other, and the electrostatic ink layer 51 and the adhesive layer 30 are in contact with each other. The electrostatic ink layer 51 is formed so as to cover the entire primer layer 40. Therefore, the laminate 310 does not have a plain portion. However, in a modified example, the electrostatic ink layer 51 may be interrupted like the electrostatic ink layer 50 of the laminate 300 in FIG. 1, and the laminate 310 may have a plain portion.
[0059] The intermediate layer 21 may have a flexible substrate. Examples of the flexible substrate include films of biaxially oriented polypropylene (BOPP), polyethylene terephthalate (PET), oriented polyamide (OPA), and nylon (NY). The intermediate layer 21 may be, for example, a deposition film (transparent deposition film) including a resin layer such as a PET film and a barrier layer (deposition layer) on the resin layer, or may be a metal layer or a barrier film. Examples of the metal layer include aluminum foil.
[0060] The second adhesive layer 31 may have the same components and thickness as the adhesive layer 30 in Fig. 1. The material and thickness of the sealant film 20 may be as described for the sealant film 20 in the laminate 300 in Fig. 1. The other layers of the laminate 310 may be as described for the laminate 300 in Fig. 1.
[0061] The adhesive layer 30 (first adhesive layer 30) and / or the second adhesive layer 31 (adhesive composition) may contain a surface modifier that improves adhesion to the primer layer 40, the electrostatic ink layer 51, the intermediate layer 21, and the sealant film 20. When the intermediate layer 21 is a barrier layer such as a metal, the adhesive strength and seal strength between the adhesive layer 30, 31 and the barrier layer can be further increased. When the barrier layer has a metal layer (aluminum layer) such as a metal foil (aluminum foil) or a metal film (aluminum film), the adhesive layer 30, 31 (adhesive composition) contains a surface modifier, thereby further improving adhesion to the metal layer. This makes it possible to obtain a laminate 300, 310 that has a higher adhesive strength of the adhesive layer and is more excellent in tearability.
[0062] Examples of the surface modifier include those containing at least one selected from sulfamic acid, phosphoric acid, nitric acid, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, and ethyl hydroxyethyl cellulose.
[0063] The adhesive composition constituting the adhesive layer 30 may contain optional components such as additives in addition to the polyisocyanate component and the polyol component. Examples of additives include antioxidants, ultraviolet absorbers, light stabilizers, fillers, silane coupling agents, epoxy resins, catalysts, coating property improvers, leveling agents, nucleating agents, lubricants, release agents, defoamers, plasticizers, surfactants, pigments, dyes, organic fine particles, inorganic fine particles, antifungal agents, and flame retardants. The adhesive composition is solvent-free and does not contain a solvent such as an organic solvent. This reduces the environmental load and sufficiently improves the working environment. The solvent-free adhesive composition is used by heating during coating.
[0064] The adhesive strength (lamination strength) of the adhesive layer 30 (first adhesive layer 30) of the laminate 300, 310 may be 1.0 N / 15 mm width or more, 1.2 N / 15 mm width or more, or 1.5 N / 15 mm width or more. The adhesive strength (lamination strength) of the second adhesive layer 31 of the laminate 310 may be the same as the adhesive strength of the first adhesive layer 30, or may be different. The adhesive strength of the laminate 300, 310 mainly depends on the cohesive force of the electrostatic ink layer 50 and the adhesive force of the adhesive layers 30, 31. The higher the cohesive force of the electrostatic ink layer 50 and the adhesive force of the adhesive layers 30, 31, the more sufficiently the adhesive strength of the laminate 300, 310 can be increased. In such a laminate 300, 310, the electrostatic ink layer and the adhesive layer are sufficiently bonded to each other, so that the laminate 300, 310 can be prevented from peeling off from the layers due to the external force applied when tearing. Therefore, the laminates 300 and 310 have excellent tear resistance. The adhesive strength (lamination strength) of the laminates 300 and 310 may be 5.0 N / 15 mm width or less.
[0065] The adhesive strength in the present disclosure is a peel adhesive strength measured in accordance with the description of JIS K 6854-1: 1999. Specifically, it can be measured by the method described in the examples of the present disclosure.
[0066] The tearability of the laminates 300, 310 can be evaluated based on the ease of tearing when tearing the laminates 300, 310. Specifically, the tearability can be evaluated by a sensory evaluation in which the laminate is held in both hands and torn by pulling one hand away from the other to determine whether the laminate is torn smoothly or not.
[0067] The appearance of the laminate 300, 310 after tearing can be evaluated by visual inspection. The appearance after tearing may also be evaluated based on the appearance after opening a packaging bag obtained from the laminate 300, 310. The appearance after tearing can be evaluated based on the presence or absence of delamination and the presence or absence of fluctuation of the tear line when the laminate 300, 310 or the packaging bag is torn.
[0068] The seal strength when the sealant films 20 of the laminates 300, 310 are bonded together may be 15.0 N / 15 mm width or more, 20.0 N / 15 mm width or more, or 25.0 N / 15 mm width or more. When the seal strength is in this range, a packaging bag and a packaging body having sufficiently high durability can be obtained. The seal strength can be measured in accordance with JIS K 7127:1999 "Plastics - Test methods for tensile properties - Part 3: Test conditions for films and sheets". The seal strength may be 100.0 N / 15 mm width or less. The range of the seal strength may be, for example, 15.0 to 100.0 N / 15 mm width, 20.0 to 100.0 N / 15 mm width, or 25.0 to 100.0 N / 15 mm width. The tear strength of the laminates 300, 310 may be in the above-mentioned numerical range.
[0069] The tear strength of the laminate 300, 310 may be 0.9N or less, 0.8N or less, or 0.7N or less. When the tear strength is in this range, the force required to tear the laminate 300, 310 is small, and the laminate can be torn smoothly. Therefore, a laminate with even better tearability can be obtained. Such a laminate can be suitably used for packaging bags and packaging bodies. The tensile strength of the laminate can be measured based on JIS K 7128-1:1998 "Plastics - Test method for tear strength of films and sheets - Part 1: Trouser tear method". The tear strength of the laminate 300, 310 may be 0.1N or more.
[0070] The laminate of the present disclosure is not limited to the structure of Fig. 1 and Fig. 2. For example, it may have the following laminate structure. In each example, the leftmost layer is the base film 10, and the rightmost layer is the sealant film 20. In each example, each layer is arranged in order from left to right. The following third adhesive layer may be an adhesive layer similar to the adhesive layer 30 (first adhesive layer) and the second adhesive layer 31, or may be an adhesive layer different from these. The layer structure of the laminate is not limited to the following examples.
[0071] Example 1) PET film / primer layer / electrostatic ink layer / adhesive layer / LLDPE film (linear low-density polyethylene film) Example 2) Nylon film / primer layer / electrostatic ink layer / adhesive layer / LLDPE film Example 3) Transparent vapor-deposited PET film / primer layer / electrostatic ink layer / adhesive layer / CPP film (non-oriented polypropylene film) Example 4) Barrier nylon film / primer layer / electrostatic ink layer / adhesive layer / CPP film Example 5) Transparent vapor-deposited PET film / primer layer / electrostatic ink layer / first adhesive layer / PET film / second adhesive layer / CPP film Example 6) Transparent vapor-deposited PET film / primer layer / electrostatic ink layer / first adhesive layer / nylon film / second adhesive layer / CPP film Example 7) Transparent vapor-deposited PET film / primer layer / electrostatic ink layer / 1st adhesive layer / PET film / 2nd adhesive layer / nylon film / 3rd adhesive layer / CPP film Example 8) Transparent vapor-deposited PET film / primer layer / electrostatic ink layer / 1st adhesive layer / nylon film / 2nd adhesive layer / PET film / 3rd adhesive layer / CPP film Example 9) Transparent vapor-deposited PET film / primer layer / electrostatic ink layer / first adhesive layer / PET film / second adhesive layer / PET film / third adhesive layer / CPP film Example 10) OPP film / primer layer / electrostatic ink layer / adhesive layer / CPP film Example 11) OPP film / primer layer / electrostatic ink layer / adhesive layer / LLDPE film Example 12) Nylon film / primer layer / electrostatic ink layer / adhesive layer / CPP film Example 13) PET film / primer layer / electrostatic ink layer / adhesive layer / CPP film Example 14) PET film / primer layer / electrostatic ink layer / first adhesive layer / nylon film / second adhesive layer / LLDPE film Example 15) PET film / primer layer / electrostatic ink layer / first adhesive layer / aluminum foil / second adhesive layer / LDPE film Example 16) PET film / primer layer / electrostatic ink layer / first adhesive layer / aluminum foil / second adhesive layer / nylon film / third adhesive layer / LLDPE film
[0072] <Method of manufacturing laminate> An example of a method for producing a laminate is described below. In this example, a laminate 300 shown in Fig. 1 is produced. The method includes the steps of forming a primer layer 40 on one side of a base film 10, printing an electrostatic ink composition on the primer layer 40 to form an electrostatic ink layer 50 and obtain a printed surface 52, adhering the printed surface 52 to one side of the sealant film 20 using a solventless adhesive composition containing a polyisocyanate component and a polyol component, and curing or semi-curing the adhesive composition to form an adhesive layer 30.
[0073] The primer layer 40 may be formed on one side of the substrate film 10 by flexographic printing or gravure printing. The primer layer 40 may be formed by crosslinking a resin raw material with a crosslinking agent. Crosslinking may be performed by irradiating with ultraviolet light, heat, ionizing radiation such as an electron beam, or non-ionizing radiation such as microwave radiation. The printing of the electrostatic ink composition may be performed by electrostatic printing using a digital printer. As the digital printer, for example, the "Indigo 20000 label and packaging digital printer" manufactured by HP may be used. In this manner, the electrostatic ink layer 50 is formed, and the printing surface 52 is obtained.
[0074] The adhesive composition may be used to bond the printed surface 52 and one side of the sealant film 20 together as follows. For example, a roll coater made up of a combination of multiple rolls is used to apply the adhesive composition, which has been heated to about 40 to 90°C and melted, to the printed surface 52 of the base film 10 or one side of the sealant film 20. Thereafter, the adhesive composition and the lamination surface of the other base material are laminated together using a nip roll so that the adhesive composition on the printed surface 52 or the adhesive composition on the sealant film 20 faces the lamination surface of the other base material. The raw roll thus obtained is aged. The adhesive composition is cured by the aging process, and the adhesive layer 30 is formed. In this way, a laminate 300 can be produced that includes the base film 10, the primer layer 40, the electrostatic ink layer 50, the adhesive layer 30, and the sealant film 20 in this order. The aging temperature may be 20 to 50°C, and the aging time may be 0.5 to 5 days.
[0075] When manufacturing the laminate 310, the sealant film 20 is replaced with the intermediate layer 21 in the above-mentioned process, and the adhesive composition that has been heated to, for example, about 40 to 90°C and melted is further applied to the surface of the intermediate layer 21 opposite to the adhesive layer 30. The application of the adhesive composition here may also be performed by a roll coater combining a plurality of rolls. Thereafter, the applied adhesive composition and the sealant film 20 are bonded to each other using a nip roll so that the applied adhesive composition and the sealant film 20 face each other. The raw roll thus obtained is aged. The adhesive composition is cured or semi-cured by a urethane reaction by aging, and the second adhesive layer 31 containing a cured product is formed. Aging to obtain the first adhesive layer 30 and the second adhesive layer 31 may be performed simultaneously. In this way, the laminate 310 having the base film 10, the primer layer 40, the electrostatic ink layer 50, the first adhesive layer 30, the intermediate layer 21, the second adhesive layer 31, and the sealant film 20 in this order can be manufactured. The laminates according to the respective modified examples can be manufactured in the same manner as the laminates 300 and 310.
[0076] The laminates 300 and 310 thus manufactured have the configurations and properties as described above. The explanation of the laminates 300 and 310 and their modified examples also applies to the above-mentioned example of the manufacturing method.
[0077] The laminate 300, 310 has a printed surface 52 printed by digital printing (electrostatic printing), which allows for a sufficiently high degree of freedom in design. In addition, the use of a solvent-free adhesive composition allows for a sufficient reduction in environmental impact. And, even though such an electrostatically printed layer and a solvent-free adhesive composition are used, the laminate 300, 310 has sufficiently excellent tearability. Such laminate 300, 310 is preferably used as a packaging material. The laminate 300, 310 may be used as a packaging material to produce a packaging bag or package.
[0078] <Packaging bags and packaging> FIG. 3 is a plan view showing an example of a packaging bag and a package formed using the above-mentioned laminate. The packaging bag 100 is formed by bonding the sealant films 20 of a pair of laminates 300 (310) together. The surface 300A on the base film 10 side becomes the outer surface of the packaging bag 100. The packaging bag 100 includes a sealed portion 101 formed by bonding the peripheries of a pair of film-like, substantially rectangular laminates 300 (310) together, and a storage portion 102 formed between the pair of laminates 300 (310) by the sealed portion 101. That is, the side end portion, lower end portion, and upper end portion of the packaging bag 100 are sealed by the sealed portion 101. The packaging bag 100 includes a storage portion 102 in which a packaged item (e.g., food) is stored in a non-sealed portion (sheet portion) surrounded by the sealed portion 101. The sealed portion 101 at the lower end portion may be sealed after the packaged item is filled in the storage portion 102. The seal portion 101 is formed by heat sealing two pieces of the sealant film 20 together.
[0079] It is not essential that the pair of packaging materials constituting the packaging bag 100 have the same layer structure, and for example, the pair of packaging materials may be composed of laminates having different layer structures.
[0080] The packaging bag 100 may be provided with an opening means 120 for facilitating opening. The opening means has a pair of easy-to-open processed parts 124 consisting of V-shaped notches formed in the sealed part 101 at the side end, and a half-cut line 121 that serves as a slitting path between the pair of easy-to-open processed parts 124. The half-cut line 121 can be formed using a laser. The easy-to-open processed parts 124 are not limited to V-shaped notches, and may be U-shaped or I-shaped notches, or may be a group of scars.
[0081] The packaging bag 100 has sufficiently excellent tearability when opened because it includes the laminates 300 and 310. Such a packaging bag 100 can be suitably used as a package.
[0082] The packaging body 200 includes a packaging bag 100 and an object to be contained in the container 102 of the packaging bag 100. The object to be contained is not particularly limited and may be a solid object, a liquid object, or a mixture thereof. Examples of the object to be contained include food, beverages, medicines, electronic devices, etc. The packaging body 200 includes the packaging bag 100 including the laminates 300, 310, and therefore has sufficiently excellent tearability when opened.
[0083] <Method of manufacturing packaging bag and packaging body> The procedure for manufacturing the packaging bag 100 and the packaging body 200 using the laminate 300 will be described below. A pair of laminates 300 cut into a predetermined shape is prepared as packaging materials. The sealant films 20 provided on one side of each laminate 300 are placed opposite each other, and the sealant films 20 are bonded together. This forms a sealed portion 101 at the upper end and side end, and forms a non-sealed portion surrounded by the sealed portion 101 in a U-shape. In this way, a packaging bag 110 in which only the upper end (or only the lower end) is unsealed is obtained as shown in FIG. 4. In some examples, the packaging bag of this embodiment may not have a portion of the periphery sealed as shown in FIG. 4.
[0084] Next, the packaged item is filled from the unsealed upper end (or lower end). After that, the laminates 300 are bonded together at the upper end (or lower end) to form a seal portion 101 at the upper end (or lower end). In this manner, a package 200 including a packaging bag 100 and the packaged item contained therein can be manufactured.
[0085] The packaging bag 100 and the packaging body 200 are manufactured using the laminates 300, 310. Therefore, while reducing the environmental impact, the packaging body 200 has excellent tearability and allows for a high degree of freedom in design, which can increase consumer purchasing interest.
[0086] Although several examples have been described above, the present embodiment is not limited to the above examples. The shape of the packaging bag may be, for example, a four-sided bag, a zipper bag, a standing bag, a gusset bag, a two-sided bag, a three-sided bag, a palm-shaped bag, etc.
[0087] The present disclosure includes the following embodiments and modifications thereof. [1] A laminate comprising a base film, a primer layer, an adhesive layer, and a sealant film in this order, and a printed surface of an electrostatic ink composition adhered to the adhesive layer, The adhesive layer comprises a solventless adhesive composition containing a polyol component and a polyisocyanate component, a cured product thereof, or a mixture thereof; A laminate, wherein the adhesive strength of the adhesive layer is 1.0 N / 15 mm width or more. [2] The laminate according to [1], wherein the polyisocyanate component includes a derivative of hexamethylene diisocyanate. [3] The laminate according to [1] or [2], having a tear strength of 0.9 N or less. [4] The laminate according to any one of [1] to [3], wherein the ink coverage of the printed surface is 500% or less. [5] The laminate according to [2], wherein the polyisocyanate component further contains a polyisocyanate different from the derivative of hexamethylene diisocyanate. [6] The laminate according to [2], wherein the derivative of hexamethylene diisocyanate includes a bifunctional derivative of hexamethylene diisocyanate and a trifunctional derivative of hexamethylene diisocyanate. [7] The laminate according to [6], wherein the content of the trifunctional derivative is higher than the content of the bifunctional derivative. [8] The laminate according to any one of [1] to [7], wherein a mass ratio of the polyisocyanate component to the polyol component is 1 or more. [9] The laminate according to any one of [1] to [8], wherein the polyol component contains a polyether polyol.
[10] The laminate according to any one of [1] to [9], wherein the adhesive composition contains a surface modifier.
[11] A step of forming a primer layer on one side of a substrate film; printing an electrostatic ink composition on the primer layer to obtain a printed surface; a step of adhering the printed surface and a substrate including a sealant film using a solventless adhesive composition including a polyisocyanate component and a polyol component; and curing or semi-curing the adhesive composition to form an adhesive layer having an adhesive strength of 1.0 N / 15 mm width or more.
[12] The method for producing a laminate according to
[11] , wherein the polyisocyanate component includes a derivative of hexamethylene diisocyanate.
[13] A method for producing a laminate according to
[11] or
[12] , wherein the tear strength is 0.9 N or less.
[14] The method for producing a laminate according to any one of
[11] to
[13] , wherein the ink coverage of the printed surface is 500% or less.
[15] A packaging bag, which is constructed by heat-sealing the sealant films in the laminate according to any one of the above [1] to
[10] .
[16] A packaging body comprising the packaging bag described in
[15] above and an item contained in the storage portion of the packaging bag. EXAMPLES
[0088] The present disclosure will be described in more detail with reference to examples, comparative examples, and reference examples, but the present disclosure is not limited to the following examples.
[0089] <Evaluation of laminates using adhesive 1> Example 1 [Laminated body production] A commercially available biaxially oriented polypropylene film (OPP film, thickness: 30 μm) was prepared as a substrate film. An aqueous primer resin (resin containing polyethyleneimine, manufactured by Michelman, product name: DP050) was applied to one side of this OPP film to form a primer layer. At this time, the amount of aqueous polyethyleneimine applied was 0.10 to 0.18 g / m 2 The water-based primer resin was applied to the OPP film so that the adhesive strength was as follows:
[0090] An electrostatic ink composition was applied to the surface of the primer layer using a digital printer (HP Indigo 20000 label and packaging digital printer) to form an electrostatic ink layer. Four types of ink compositions, yellow (Y), magenta (M), cyan (C), and W (white), were prepared, and an electrostatic ink layer was formed so that the ink coverage rate of W was 100%. As the electrostatic ink composition, an electrostatic ink composition (HP Indigo Electroink) containing a thermoplastic resin containing a copolymer of ethylene acrylic acid and ethylene methacrylic acid was used.
[0091] As the polyisocyanate component, a derivative of diphenylmethane isocyanate (MDI) (MDI derivative, manufactured by Mitsui Chemicals, Inc.), a derivative of hexamethylene diisocyanate (HDI derivative I, manufactured by Mitsui Chemicals, Inc.), and a derivative of hexamethylene diisocyanate (HDI derivative II, manufactured by Mitsui Chemicals, Inc.) were prepared. The HDI derivative I contained a bifunctional derivative of hexamethylene diisocyanate. The HDI derivative II contained a trifunctional derivative of hexamethylene diisocyanate. The MDI derivative, HDI derivative I, and HDI derivative II were mixed in a mass ratio of MDI derivative:HDI derivative I:HDI derivative II = 100:14:28 to prepare a polyisocyanate component.
[0092] A polyether polyol (manufactured by Mitsui Chemicals, Inc., product name: XRN-21B) was prepared as the polyol component. The polyol component and the polyisocyanate component were mixed so that the mass ratio of the polyol component to the polyisocyanate component was 142 / 65 (≒2.18), and a surface modifier was further added to prepare an adhesive composition. This adhesive composition was designated as Adhesive 1. This adhesive composition was heated to about 40°C and applied to one side of an electrostatic ink layer formed on a substrate film using a roll coater to form a coating film having a predetermined thickness. The amount of adhesive composition applied was about 2.0 g / m 2 This coating film and a commercially available non-oriented polypropylene film (CPP film, thickness: 30 μm) as a sealant film were overlapped so as to face each other, and the electrostatic ink layer (or primer layer) on the base film and the CPP film were bonded via the coating film (adhesive composition) using a nip roll.
[0093] Thereafter, aging was performed at 45° C. for 2 days to cure or semi-cure the adhesive composition of the coating film. In this manner, a laminate having an OPP film, a primer layer, an electrostatic ink layer, an adhesive layer, and a CPP film in this order was obtained. This was designated as the laminate of Example 1.
[0094] [Adhesive strength measurement] The adhesive strength of the prepared laminate was measured in accordance with JIS K 6854-1:1999. Specifically, the prepared laminate was cut into a width of 15 mm to obtain a measurement sample. After peeling the edge of the measurement sample between the OPP film and the CPP film, the peel adhesion strength of the laminate was measured using a tensile tester under conditions of an angle of 90°, a tensile speed of 300 mm / min, and room temperature. This peel adhesion strength was defined as the adhesive strength. The measurement results are shown in Table 1.
[0095] [Evaluation of tearability] The tearability of the prepared laminate was evaluated by a sensory evaluation in which the prepared laminate was actually torn. The sensory evaluation was performed according to the following procedure. The prepared laminate was held with both hands, and when the laminate was torn by pulling one hand away from the other, it was judged whether the laminate was torn smoothly or not. The results of the sensory evaluation were judged according to the following criteria based on the ease of tearing the laminate. The results are shown in Table 1. A: There was little resistance when tearing the laminate, and it could be torn smoothly by hand. B: There was a large resistance when tearing the laminate, and it was not possible to tear it smoothly by hand.
[0096] (Reference Example 1, Examples 2 to 4) A laminate was produced in the same manner as in Example 1, except that the ink coverage was as shown in Table 1. The laminate with an ink coverage of 0% did not have an electrostatic ink layer and was therefore designated Reference Example 1. The adhesive strength was measured and the tearability was evaluated in the same manner as in Example 1. The results were as shown in Table 1.
[0097] [Seal strength measurement] A pair of laminates having the same ink coverage were heat-sealed so that the sealant films (CPP films) overlapped each other to form a heat-sealed portion. The heat-sealing conditions were 160°C, 0.2 MPa, and 0.5 seconds. The CPP films were thus welded to prepare a 15 mm wide measurement sample. The seal strength of the seal portion of the measurement sample thus prepared was measured in accordance with JIS K 7127:1999. The measurement was performed using a tensile tester under the conditions of a peel angle of 90°, a tensile speed of 300 mm / min, and room temperature (20°C), to measure the peel strength between the heat seals. This peel strength was defined as the seal strength. The measurement results were as shown in Table 1.
[0098] [Tear strength measurement] The tear strength of the laminate was measured according to JIS K 7128-1:1999 for Reference Example 1, Example 3, and Example 4. The measurement was performed by pulling the laminate vertically using a tensile tester at a test speed of 200 mm / min and at room temperature (20°C) to measure the force required to completely tear the laminate in the MD direction. The measurement results are shown in Table 1.
[0099] [Evaluation of appearance after tearing] The sealant layers of each laminate were placed facing each other and heat sealed to obtain a packaging bag with four sealed sides (as shown in FIG. 3). An I-shaped notch was provided on one of the sealed sides. Each packaging bag was opened starting from the notch, and the appearance after tearing was visually inspected to evaluate the appearance after tearing. The appearance after tearing was evaluated based on the cleanliness of the tear line, according to the following evaluation criteria. The results are shown in Table 1. A: No delamination of the laminate was observed, and there was little fluctuation of the tear line. B: No delamination of the laminate was observed, but the tear line was fluctuating. C: Delamination of the laminate was observed and the tear line was fluctuating.
[0100] For reference, an example with an evaluation result of "A" according to the above evaluation criteria is shown in FIG. 5, and an example with an evaluation result of "C" according to the above evaluation criteria is shown in FIG. 6. In the laminate 60 of FIG. 5, a tear line T was formed by pulling the lower end 62 toward the front side of the drawing with respect to the upper end 61. As shown in FIG. 5, the laminate 60 with an evaluation result of "A" had little fluctuation of the tear line T. On the other hand, in the laminate 160 of FIG. 6 with an evaluation result of "C", a positional shift occurred between the tear line T1 of the upper end 161 and the tear line T2 of the lower end 162, and both the tear lines T1 and T2 fluctuated. In addition, delamination 170 was observed. It is considered that such positional shift and delamination occur because, when a laminate with low adhesive strength is torn, the external force used for tearing is not concentrated on the tear line, and the external force for tearing cannot be fully utilized.
[0101] <Evaluation of laminates using adhesive 2> Example 5 A solventless adhesive composition was prepared in the same manner as in Example 1, except that no surface modifier was added. This adhesive composition was designated adhesive 2. Using adhesive 2 as the adhesive composition, a laminate having an OPP film, a primer layer, an electrostatic ink layer, an adhesive layer, and a CPP film in this order was obtained in the same manner as in Example 1. Measurement of adhesive strength, evaluation of tearability, and evaluation of appearance after tearing were performed in the same manner as in Example 1. The results were as shown in Table 1.
[0102] (Reference Example 2, Examples 6 to 8) A laminate was produced in the same manner as in Example 5, except that the ink coverage was as shown in Table 1. The laminate with an ink coverage of 0% did not have an electrostatic ink layer, and was designated Reference Example 2. Measurement of adhesive strength, evaluation of tearability, and evaluation of appearance after tearing were performed in the same manner as in Example 1. Furthermore, the seal strength was measured in the same manner as in Example 2. For Reference Example 2, Examples 7, and 8, the tear strength was measured in the same manner as in Example 3. The results are shown in Table 1.
[0103] <Evaluation of laminate using adhesive 3> Example 9 A laminate was produced in the same manner as in Example 1, except that a commercially available solvent-free adhesive composition was used instead of the adhesive composition used in Example 1. This adhesive composition was prepared by blending polyether polyol (manufactured by Toyo Morton Co., Ltd., product name: EA-N373B) as a base agent and aromatic polyisocyanate (manufactured by Toyo Morton Co., Ltd., product name: EA-N373A) as a curing agent. This adhesive composition was designated as adhesive 3. The blending ratio (mass basis) of each component was (base agent):(curing agent) = 50:100. Measurement of adhesive strength, evaluation of tearability, and evaluation of appearance after tearing were performed in the same manner as in Example 1. The results were as shown in Table 1.
[0104] (Reference Example 3, Example 10) A laminate was produced in the same manner as in Example 9, except that the ink coverage was as shown in Table 1. The laminate with an ink coverage of 0% did not have an electrostatic ink layer, and was designated Reference Example 3. Measurement of adhesive strength, evaluation of tearability, and evaluation of appearance after tearing were performed in the same manner as in Example 1. Furthermore, the seal strength was measured in the same manner as in Example 2. Furthermore, for Reference Example 4, tear strength was measured in the same manner as in Example 3. The measurement results are shown in Table 1.
[0105] Comparative Example 1 A laminate was produced in the same manner as in Example 9, except that the ink coverage was as shown in Table 1. Measurement of adhesive strength, evaluation of tearability, measurement of seal strength, measurement of tear strength, and evaluation of appearance after tearing were performed in the same manner as in Example 4. The results of each measurement are shown in Table 1.
[0106] <Evaluation of laminates using adhesive 4> Comparative Example 2 An organic solvent-based adhesive composition with a solid content concentration of 33% by mass was prepared by blending an aliphatic polyester polyol (manufactured by Mitsui Chemicals, Inc., product name: Takelac A626) as a base agent, a polyisocyanate (manufactured by Mitsui Chemicals, Inc., product name: Takenate A65) as a curing agent, and ethyl acetate as a solvent. This adhesive composition was named Adhesive 4. The blending ratio (mass basis) of each component was (base agent):(curing agent)=16:1.
[0107] A primer layer was formed on a base film (OPP film) in the same manner as in Example 1. Then, an electrostatic ink composition was applied to a part of the surface of the primer layer using a digital printer (Indigo20000 label and packaging digital printer manufactured by HP) to form an electrostatic ink layer. The ink coverage of the electrostatic ink layer was as shown in Table 1.
[0108] The organic solvent-based adhesive composition prepared as described above was applied to the electrostatic ink layer using a dry laminating device, and then hot air drying was performed to form a coating film consisting of only nonvolatile components. The coating amount of the nonvolatile coating film was about 2.0 g / m 2 The coating film and the sealant film (CPP film) used in Example 1 were overlapped so as to face each other, and the electrostatic ink layer on the base film and the sealant film were bonded via the coating film using a nip roll. The coating film was then cured by aging at 40°C for 2 days. By such a dry lamination method, a laminate of Comparative Example 2 having an OPP film, a primer layer, an electrostatic ink layer, an adhesive layer, and a CPP film in this order was obtained. The laminate of Comparative Example 1 differs from the laminate of Example 1 in that adhesive 4, which is an organic solvent-based adhesive composition, is used. The adhesive strength of the laminate of Comparative Example 2 was measured, the tearability was evaluated, and the appearance after tearing was evaluated in the same procedure as in Example 1. The results were as shown in Table 1.
[0109] (Reference Example 4, Comparative Examples 3 to 5) A laminate was produced in the same manner as in Comparative Example 2, except that the ink coverage was as shown in Table 1. The laminate with an ink coverage of 0% did not have an electrostatic ink layer, and was designated Reference Example 4. Measurement of adhesive strength, evaluation of tearability, and evaluation of appearance after tearing were performed in the same manner as in Example 1. Furthermore, the seal strength was measured in the same manner as in Example 2. For Reference Example 4 and Comparative Examples 4 and 5, the tear strength was measured in the same manner as in Example 3. The results are shown in Table 1.
[0110] [Table 1]
[0111] Each value in Table 1 indicates adhesive strength, sealing strength, or tear strength. The symbols "A", "B", and "C" indicate the appearance evaluation after tearing, or the evaluation of tearability. Columns where no measurement was performed are marked with "-". The column below each value and symbol indicates the location of peeling when each strength was measured. "OPP surface layer" indicates that the surface layer of the OPP film has migrated to the adhesive layer. "Ink surface layer" indicates that the surface layer of the electrostatic ink layer has migrated to the base film side. "Ink coagulation" indicates that the electrostatic ink layer itself has broken. "OPP / ink" indicates that the interface between the OPP film and the electrostatic ink layer has peeled off. "OPP / ad" indicates that the interface between the OPP film and the adhesive layer has peeled off. "OPP cut" indicates that the OPP film has been cut. "Ink / ad" indicates that the interface between the electrostatic ink layer and the adhesive layer has peeled off. "Triangular peeling" indicates that peeling has occurred within the laminate, not between the sealant layers. In addition, "OPP / ink", "OPP / ad", and "ink / ad" fall under the category of interlayer delamination.
[0112] In the case of adhesives 1 and 2, the adhesive strength was 1.0 N / 15 mm width or more at any ink coverage rate, and the laminate had good tearability and appearance after tearing. When a laminate with high adhesive strength is torn, delamination is unlikely to occur because the adhesive layer is sufficiently adhered to the electrostatic ink layer. In addition, as the ink coverage rate increases, the thickness of the electrostatic ink layer increases, so the adhesive strength decreases and delamination is likely to occur, and the tearability tends to deteriorate. However, in the case of adhesives 1 and 2, even when the ink coverage rate is 300% or more, the adhesive strength was good and the appearance after tearing was also kept good. In addition, when the ink coverage rate is 200% or less, the adhesive strength was higher and the adhesive had good tearability. On the other hand, in the case of adhesive 3, as shown in Comparative Example 1, when the ink coverage rate is 400%, the adhesive strength was 0.8 N / 15 mm width, the tearability was poor, and delamination occurred, resulting in a poor appearance after tearing. However, because the adhesive strength improved when the ink coverage was reduced, even adhesive 3 had good tear properties when the ink coverage was less than 400%.
[0113] From the above results, it can be said that a laminate with an adhesive strength of 1.0 N / 15 mm width or more has excellent tearability. Therefore, it was confirmed that a laminate having an electrostatic ink layer and a solventless adhesive layer and an adhesive strength of 1.0 N / 15 mm width or more has excellent tearability while reducing the environmental load.
[0114] <Evaluation of laminates using adhesive 1> Example 11 A commercially available polyethylene terephthalate film (PET film, thickness: 12 μm) was prepared as a substrate film. One side of this PET film was coated with an aqueous primer resin (a resin containing polyethyleneimine, manufactured by Michelman, product name: DP050) to form a primer layer. At this time, the coating amount of aqueous polyethyleneimine was 0.10 to 0.18 g / m 2 The water-based primer resin was applied to the PET film so that the thickness of the water-based primer resin was 100 μm.
[0115] Using a digital printer (HP Indigo 20000 label and packaging digital printer), an electrostatic ink composition was applied to the surface of the primer layer in the same manner as in Example 1 to form an electrostatic ink layer. As the electrostatic ink composition, an electrostatic ink composition (HP Indigo Electroink) containing a thermoplastic resin containing a copolymer of ethylene acrylic acid and ethylene methacrylic acid was used. The ink coverage was as shown in Table 2.
[0116] The adhesive 1 prepared in Example 1 was used as an adhesive composition and applied to one side of an electrostatic ink layer formed on a substrate film in the same manner as in Example 1 to form a first coating film having a predetermined thickness. This first coating film was laminated facing a commercially available aluminum foil (AL foil, manufactured by Luoyang Wanji Aluminum Processing Co., Ltd., product number: 8079, thickness: 7 μm) as an intermediate layer, and the electrostatic ink layer on the substrate film and the AL foil were bonded via the first coating film (adhesive composition) using a nip roll.
[0117] Next, the adhesive composition was similarly applied to the surface of the AL foil (the surface opposite to the substrate film side) to form a second coating film having a predetermined thickness. The amount of the adhesive composition applied was about 2.0 g / m 2 A commercially available low-density polyethylene film (LDPE film, thickness: 60 μm) was laminated as a sealant film on this second coating film so as to face each other, and the AL foil and the sealant film were bonded via the second coating film (adhesive composition) using a nip roll.
[0118] Thereafter, aging was performed at 45° C. for 2 days to cure or semi-cure the adhesive composition of the first coating film and the second coating film. In this manner, a laminate having a PET film, a primer layer, an electrostatic ink layer, a first adhesive layer, an AL foil, a second adhesive layer, and an LDPE film in this order was obtained. This was designated as the laminate of Example 12.
[0119] In the same manner as in Example 1, the edge of the measurement sample was peeled between the PET film and the AL foil in the laminate of Example 11, and the adhesive strength of the first adhesive layer was measured. In addition, in the same manner as in Example 1, the tearability was evaluated, and the appearance after tearing was evaluated. The results are shown in Table 2. In addition, the adhesive strength of the second adhesive layer was measured in the same manner as the adhesive strength between the AL foil and the LDPE film. The adhesive strength of the second adhesive layer was 2.8 N / 15 mm width.
[0120] (Reference Example 5, Examples 12 to 14) A laminate was produced in the same manner as in Example 11, except that the ink coverage was as shown in Table 2. The laminate with an ink coverage of 0% did not have an electrostatic ink layer, and was designated Reference Example 5. Measurement of adhesive strength, evaluation of tearability, and evaluation of appearance after tearing were performed in the same manner as in Example 11. Furthermore, the seal strength was measured in the same manner as in Example 2. For Reference Example 5, Examples 13, and 14, the tear strength was measured in the same manner as in Example 3. The results are shown in Table 2.
[0121] <Evaluation of laminates using adhesive 2> Example 15 A laminate was produced in the same manner as in Example 11, except that the adhesive composition was the adhesive 2 used in Example 5, and a laminate having a PET film, a primer layer, an electrostatic ink layer, a first adhesive layer, an AL foil, a second adhesive layer, and an LLDPE film in this order was obtained. The adhesive strength of the first adhesive layer was measured, the tearability was evaluated, and the appearance after tearing was evaluated in the same manner as in Example 11. The results are shown in Table 2. In addition, the adhesive strength of the second adhesive layer was measured in the same manner as the adhesive strength between the AL foil and the LDPE film. The adhesive strength of the second adhesive layer was 2.3 N / 15 mm width.
[0122] (Reference Example 6, Example 16) A laminate was produced in the same manner as in Example 15, except that the ink coverage was as shown in Table 2. The laminate with an ink coverage of 0% did not have an electrostatic ink layer, and was designated Reference Example 6. The adhesive strength of the first adhesive layer was measured, the tearability was evaluated, and the appearance after tearing was evaluated in the same manner as in Example 11. The seal strength was also measured in the same manner as in Example 2. Furthermore, for Reference Example 6, the tear strength was measured in the same manner as in Example 3. The results are shown in Table 2.
[0123] Comparative Example 7 A laminate was produced in the same manner as in Example 15, except that the ink coverage was as shown in Table 2. Measurement of adhesive strength, evaluation of tearability, measurement of seal strength, measurement of tear strength, and evaluation of appearance after tearing were performed in the same manner as in Example 4. The results of each measurement are shown in Table 2.
[0124] <Evaluation of laminate using adhesive 3> (Example 17) A laminate was produced in the same manner as in Example 11, except that the adhesive composition was the adhesive 3 used in Example 9, and a laminate having a PET film, a primer layer, an electrostatic ink layer, a first adhesive layer, an AL foil, a second adhesive layer, and an LLDPE film in this order was obtained. The adhesive strength of the first adhesive layer was measured, the tearability was evaluated, and the appearance after tearing was evaluated in the same manner as in Example 11. The results are shown in Table 2. In addition, the adhesive strength of the AL foil and the LDPE film was measured in the same manner as the adhesive strength of the second adhesive layer. The adhesive strength of the second adhesive layer was 3.5 N / 15 mm width.
[0125] (Reference Example 7, Example 18) A laminate was produced in the same manner as in Example 17, except that the ink coverage was as shown in Table 2. The laminate with an ink coverage of 0% did not have an electrostatic ink layer, and was therefore designated Reference Example 7. Measurement of adhesive strength, evaluation of tearability, and evaluation of appearance after tearing were carried out in the same manner as in Example 1. Furthermore, the seal strength was measured in the same manner as in Example 2. Furthermore, for Reference Example 7, the tear strength was measured in the same manner as in Example 3. The measurement results were as shown in Table 2.
[0126] Comparative Example 8 A laminate was produced in the same manner as in Example 17, except that the ink coverage was as shown in Table 2. Measurement of adhesive strength, evaluation of tearability, measurement of seal strength, measurement of tear strength, and evaluation of appearance after tearing were performed in the same manner as in Example 4. The results of each measurement are shown in Table 2.
[0127] <Evaluation of laminates using adhesive 4> Comparative Example 9 A primer layer was formed on a substrate film (PET film) in the same manner as in Example 11. Then, an electrostatic ink composition was applied to a part of the surface of the primer layer using a digital printer (Indigo20000 label and packaging digital printer manufactured by HP) to form an electrostatic ink layer. The ink coverage of the electrostatic ink layer was as shown in Table 2.
[0128] The adhesive 4 used in Comparative Example 2 was applied to the electrostatic ink layer using a dry laminating device, and then hot air drying was performed to form a first coating film consisting of only nonvolatile components. The coating amount of the nonvolatile coating film was about 2.0 g / m 2 This first coating film and the commercially available aluminum foil used in Example 12 were overlapped so as to face each other, and the electrostatic ink layer on the base film and the aluminum foil were bonded via the first coating film (adhesive composition) using a nip roll.
[0129] Next, the adhesive composition was applied in the same manner to the surface of the AL foil (the surface opposite to the substrate film side) using a dry laminator to form a second coating film having a predetermined thickness. The amount of the adhesive composition applied was about 2.0 g / m 2 A commercially available low-density polyethylene film (LDPE film, thickness: 60 μm) was laminated as a sealant film on this second coating film so as to face each other, and the AL foil and the sealant film were bonded via the second coating film (adhesive composition) using a nip roll.
[0130] Thereafter, aging was performed at 40°C for 2 days to cure or semi-cure the adhesive composition of the first coating film and the second coating film. A laminate having a PET film, a primer layer, an electrostatic ink layer, a first adhesive layer, an AL foil, a second adhesive layer, and an LDPE film in this order was obtained by such a dry lamination method. This was the laminate of Comparative Example 9. In the same procedure as in Example 1, the end of the measurement sample was peeled between the PET film and the AL foil in the laminate of Comparative Example 9 to measure the adhesive strength of the first adhesive layer. In addition, in the same procedure as in Example 1, the evaluation of the tearability and the appearance evaluation after tearing were performed. The results were as shown in Table 2. In addition, the adhesive strength of the AL foil and the LDPE film was measured in the same manner as the adhesive strength of the second adhesive layer. The adhesive strength of the second adhesive layer was 4.5N / 15mm width.
[0131] (Reference Example 8, Comparative Examples 10 to 12) Except for the ink coverage rate shown in Table 2, a laminate was prepared in the same manner as in Comparative Example 2, and the tear property was evaluated in the same manner as in Comparative Example 9. The laminate with an ink coverage rate of 0% was designated as Reference Example 8 because it did not have an electrostatic ink layer. For Reference Example 8 and Comparative Examples 11 and 12, the adhesive strength was measured and the appearance after tearing was evaluated in the same manner as in Comparative Example 9. In addition, the seal strength of each laminate was measured in the same manner as in Example 2. For Reference Example 8 and Comparative Examples 11 and 12, the tear strength was measured in the same manner as in Example 3. The measurement results were as shown in Table 2.
[0132] [Table 2]
[0133] The values in each column in Table 2 indicate the adhesive strength, seal strength, or tear strength. The symbols "A", "B", and "C" indicate the evaluation of tearability or the evaluation of appearance after tearing. Columns where no measurement was performed are marked "-". The adhesive strength of each electrostatic ink layer indicates the adhesive strength of the first adhesive layer. The column below each value or symbol indicates the location of peeling when each strength was measured. In Table 2, "PET cut" indicates that the PET film was cut. "AL cut" indicates that the AL foil was cut. "ad cohesion" indicates that the first adhesive layer itself was broken. "ad / AL" indicates that the interface between the first adhesive layer and the aluminum foil was peeled off. "Cohesion peeling" indicates that peeling occurred at the first adhesive layer or the second adhesive layer. "ad / AL" corresponds to interlayer peeling.
[0134] In the case of adhesive 1, the adhesive strength was 1.0 N / 15 mm width or more at any ink coverage rate, and the adhesive had good tearability. When a laminate with high adhesive strength is torn, delamination is unlikely to occur because the adhesive layer is sufficiently adhered to the electrostatic ink layer. In addition, as the ink coverage rate increases, the thickness of the electrostatic ink layer increases, so the adhesive strength decreases, delamination is likely to occur, and tearability tends to deteriorate. However, in the case of adhesive 1, even when the ink coverage rate is 300% or more, the adhesive had good tearability, and the appearance after tearing was also well maintained. In addition, when the ink coverage rate is 200% or less, the adhesive strength was higher and the adhesive had good tearability. On the other hand, in the case of adhesives 2 and 3, when the ink coverage rate is 400%, the adhesive strength was low, the tearability was poor, and delamination occurred in the laminate after tearing, as shown in Comparative Example 7 and Comparative Example 8. However, when the ink coverage was less than 400%, the adhesive strength was improved, and therefore, even adhesives 2 and 3 had good tear properties when the ink coverage was less than 400%.
[0135] From the above results, it can be said that a laminate with an adhesive strength of 1.0 N / 15 mm width or more has excellent tearability. Therefore, it was confirmed that a laminate having an electrostatic ink layer and a solventless adhesive layer and an adhesive strength of 1.0 N / 15 mm width or more has excellent tearability while reducing the environmental load.
[0136] In Examples 11 to 14, it was confirmed that the adhesive strength was 1.0 N / 15 mm width or more at any ink coverage rate, and the laminate did not peel off after tearing and showed excellent appearance. On the other hand, as shown in Comparative Examples 7 and 8, it was confirmed that when the adhesive strength was low, the laminate peeled off after tearing and the appearance after tearing became poor. Therefore, it can be said that a laminate having an adhesive strength of 1.0 N / 15 mm width or more has excellent appearance after tearing. Therefore, it was confirmed that a laminate having excellent appearance after tearing can be obtained when an electrostatic ink layer and a solventless adhesive composition are used and the adhesive strength is 1.0 N / 15 mm width or more.
[0137] From the results of each of the above-mentioned Examples and Comparative Examples, when an electrostatic ink layer and a solvent-free adhesive composition are used, the laminate of the present disclosure has a sufficiently high adhesive strength and good tearability. Therefore, the laminate of the present disclosure can be suitably used for packaging bags and packaging bodies. [Industrial Applicability]
[0138] According to the present disclosure, it is possible to provide a laminate having an electrostatic ink layer, which has excellent tearability while reducing the environmental impact, and a manufacturing method thereof. It is also possible to provide a packaging bag and a packaging body including such a laminate. [Explanation of symbols]
[0139] 10...base film, 20...sealant film, 21...intermediate layer, 30...adhesive layer (first adhesive layer), 31...adhesive layer (second adhesive layer), 40...primer layer, 50,51...electrostatic ink layer, 52...printed surface, 100,110...packaging bag, 101...sealed portion, 102...storage portion, 120...opening means, 121...half-cut line, 124...easy-open processing portion, 200...packaging body, 60,160,300,310...laminate, 61,161...upper end portion, 62,162...lower end portion, 170...interlayer peeling, T,T1,T2...tear lines.
Claims
1. A laminate comprising a substrate film, a primer layer, an adhesive layer, and a sealant film in this order, and a printed surface of an electrostatic ink composition adhered to the adhesive layer, The adhesive layer comprises a solventless adhesive composition containing a polyol component and a polyisocyanate component, a cured product thereof, or a mixture thereof; A laminate, wherein the adhesive strength of the adhesive layer is 1.0 N / 15 mm width or more.
2. The laminate of claim 1 , wherein the polyisocyanate component comprises a derivative of hexamethylene diisocyanate.
3. 3. The laminate according to claim 1 or 2, having a tear strength of 0.9 N or less.
4. 3. The laminate according to claim 1, wherein the ink coverage of the printed surface is 500% or less.
5. The laminate of claim 2 , wherein the polyisocyanate component further comprises a polyisocyanate different from the derivative of hexamethylene diisocyanate.
6. The laminate according to claim 2 , wherein the derivative of hexamethylene diisocyanate includes a bifunctional derivative of hexamethylene diisocyanate and a trifunctional derivative of hexamethylene diisocyanate.
7. The laminate according to claim 6 , wherein the content of the trifunctional derivative is higher than the content of the bifunctional derivative.
8. The laminate according to claim 1 or 2, wherein a mass ratio of the polyisocyanate component to the polyol component is 1 or more.
9. The laminate of claim 1 or 2, wherein the polyol component comprises a polyether polyol.
10. The laminate of claim 1 or 2, wherein the adhesive composition comprises a surface modifier.
11. forming a primer layer on one side of a substrate film; printing an electrostatic ink composition on the primer layer to obtain a printed surface; a step of adhering the printed surface and a substrate including a sealant film using a solventless adhesive composition including a polyisocyanate component and a polyol component; and curing or semi-curing the adhesive composition to form an adhesive layer having an adhesive strength of 1.0 N / 15 mm width or more.
12. The method of claim 11 , wherein the polyisocyanate component comprises a derivative of hexamethylene diisocyanate.
13. The method for producing a laminate according to claim 11 or 12, wherein the tear strength is 0.9 N or less.
14. The method for producing a laminate according to claim 11 or 12, wherein the ink coverage of the printed surface is 500% or less.
15. A packaging bag formed by heat-sealing the sealant films in the laminate according to claim 1 or 2.
16. A package comprising the packaging bag according to claim 15 and an item contained in the container of the packaging bag.
Citation Information
Patent Citations
Two pack curable solvent-free adhesive
JP2011162656A
flexible packaging material
JP2018530478A
Curing agent, two-component adhesive, adhesive composition, cured product, laminate and method for producing same, packing material, and packed body
WO2021024981A1